Mimicry in The Novel Divortiare Trilogy by Ika Natassa - Chaerani, Gista Salsabila; Supriyanto, Teguh; Setyaningsih, Nas Haryati (Universitas Negeri Semarang, 2022)
Mimicry towards Western nations occurs a lot in society in the era of globalization. It is also reflected in the novel Divortiare trilogy by Ika Natassa. This study aims to determine how expressions of mimicry are found in the novel Divortiare trilogy. The research approach uses a postcolonialism approach, especially mimicry, using qualitative research methods, collection methods, and analytical techniques in the form of heuristics and hermeneutics. The data in this study are text fragments that show expressions of mimicry. The things found in the research are the use of English, which is often used by characters when speaking or sending messages and when using social media, lifestyles such as drinking and clothing styles, which imitate Western society, such as wearing stilettos, which come from abroad.